(untitled) (Bangladesh Journal of Child Health, 2013)
Background: The importance of Paediatric Rheumatic Diseases (PRDs) is increasing globally day by day. These diseases are considered as important chronic cause of childhood morbidity and disability. It is recognized that early recognition and diagnosis as well as timely intervention can improve the outcome of PRDs. Objective: To estimate the pattern of PRDs and to compare the profile of JIA with other studies were done abroad. Method: Retrospective study was done in the paediatric rheumatology clinic and in patient department of Bangabandhu Sheikh Mujib Medical University (BSMMU) during the study period from July 2007-December 2012. All the patients fulfilling the ILAR classification criteria of Juvenile idiopathic arthritis (JIA), ACR classification criteria of systemic lupus erythematosus ( SLE), PReS-EULAR-PRINTO classification criteria of childhood vasculitis Bohan A, Peter JB Classification criteria for juvenile dermatomyositis (JDM) and preliminary criteria for the classification of systemic sclerosis (SS) were enrolled in this study. Results: A total of 540 patients were enrolled. Highest number of patients had JIA (77%), which was followed by SLE (10%). Among childhood vasculitis, Henoch Shonlein purpura (HSP) was predominant (4.2%) followed by Polyarteritis nodosa (1.9%) and Kawasaki Disease (0.6%). Juvenile dermatomiositis (JDM), systemic sclerosis (SS) and rheumatic fever was also found in 1.6%, 1.3% and 3% cases respectively. Polyarticular JIA was the commonest type (33 %) in this series, followed by oligoarthritis, systemic onset and enthesitis related arthritis (ERA). Conclusion: JIA was the commonest among the paediatric rheumatic diseases followed by SLE and childhood vasculitis. DOI: http://dx.doi.org/10.3329/bjch.v37i2.17267 BANGLADESH J CHILD HEALTH 2013; VOL 37 (2) : 97-101